Attacking game-patterns differences between south american and european national soccer soccer teams in the world cup 2010 - Barreira, D.; Garganta, J.; Guimarães, P.; Soares, R.; Anguera, T. (7th World Congress on Science and Football (WCSF), 2011, 2011)
In Soccer tactical patterns seems to differ according to geographical and cultural specificities of the playing teams. This study aimed to set differences in the attacking patterns between South American (A) and European (U) teams in the World Cup 2010. Method This is a lag-log study, following an observational, nomothetic and multidimensional design (Anguera, 1992). Field formats were combined with a system of categories, according to seven criteria: Start of the offensive phase; Development of defense/attack transition; Progress of ball possession; Finishing of the offensive phase; Patterns of field space position; Centre of the game/Ball position; Spatial patterns of teams interaction. The sequences were classified according to teams` geography—A and E— using the GSEQ Software. After determining the reliability (Cohen`s Kappa>0.9), 8 matches were coded. 295 attacks were registered in the A national teams; 662 attacks were reported to the E teams. Results and Discussion From the quarter- until the final phase, A teams performed an average of 59 attacks per game, 6 goals, needing 9.8 attacks to score 1 goal while E teams performed an average of 83 attacks, 15 goals and needing 5.5 attacks to score 1 goal. In the whole tournament, A and E teams scored 1.5 and 1.7 goals per game, respectively, with the same tendency for shots on target (6.2 and 6.4). Goal patterns of E teams were: (1) long pass from the defensive to the central offensive zone, followed by shot with absolute strain (z=3.13) saved by the Gk, and finishing the attack with a goal scored in the central offensive zone in 1xGk contexts (z=6.35), or with the offensive line vs. the opponent defensive line (z=2.18); (2) cross from the left offensive zone (z=8.36) preceded by ball conduction in the same zone (z=3.87). The goal patterns of A teams were dribble in the central mid-offensive zone (z=2.76), scoring in situations of 1xGk (z=3.65). In E teams shots on target occurred mainly in the central offensive zone in situations of 1xGk after dribble (z=3.89). In A teams, shots on target occurred following a corner kick (z=2.07) or an indirect free kick (z=2.14). In A teams, set plays with shot on target occurred due to individual progressing with the ball in the central offensive zone compared to E teams. Conclusion Goal patterns showed a predominantly attack through the wings in E teams and by central offensive zones in A teams.